Submesoscale CO2 variability across an upwelling front off Peru - E. E. Köhn; S. Thomsen; D. L. Arévalo-Martínez; T. Kanzow; T. Kanzow (Ocean Science, 2017)
As a major source for atmospheric CO2, the Peruvian upwelling region exhibits strong variability in surface fCO2 on short spatial and temporal scales. Understanding the physical processes driving the strong variability is of fundamental importance for constraining the effect of marine emissions from upwelling regions on the global CO2 budget. In this study, a frontal decay on length scales of 𝒪(10 km) was observed off the Peruvian coast following a pronounced decrease in down-frontal (equatorward) wind speed with a time lag of 9 h. Simultaneously, the sea-to-air flux of CO2 on the inshore (cold) side of the front dropped from up to 80 to 10 mmol m−2 day−1, while the offshore (warm) side of the front was constantly outgassing at a rate of 10–20 mmol m−2 day−1. Based on repeated ship transects the decay of the front was observed to occur in two phases. The first phase was characterized by a development of coherent surface temperature anomalies which gained in amplitude over 6–9 h. The second phase was characterized by a disappearance of the surface temperature front within 6 h. Submesoscale mixed-layer instabilities were present but seem too slow to completely remove the temperature gradient in this short time period. Dynamics such as a pressure-driven gravity current appear to be a likely mechanism behind the evolution of the front.